COMPARATIVE ANALYSIS OF FARM ECONOMIC VIABILITY ASSESSMENT METHODOLOGIES - Slavickiene, Astrida; Savickiene, Jurate (European Scientific Journal, ESJ, 2014)
The paper deals with the economic assessment methodologies the strengths and weaknesses. It was found that, farm economic viability assessment differs from country to country: that is determined by differences in the natural environment, a different support policy, return on equity, labour productivity and land productivity. Methodologies rely on 23 financial ratios and 10 non-financial indicators, including 5 recurring indicators, namely Return on Equity, Expense to Income Ratio, Debt Ratio, Net Return, and Output to Economic Size Unit Ratio. After an empiric comparative analysis of economic viability assessment methodologies was conducted, their applicability by the example of Lithuanian farms was assessed, the obtained results were compared to similar results from farms in the EU states, and it was found that, there is no best methodology of the assessment of the economic viability of agricultural holdings for Lithuania. However a combination of methodologies by J. Scott and J. H. Tobraegel would result in a more efficient assessment of the economic viability of agricultural holdings.